2011
DOI: 10.1095/biolreprod.110.090019
|View full text |Cite
|
Sign up to set email alerts
|

Conceptus-Induced Changes in the Endometrial Transcriptome: How Soon Does the Cow Know She Is Pregnant?1

Abstract: This study sought to determine the earliest response of the bovine uterine endometrium to the presence of the conceptus at key developmental stages of early pregnancy. There were no detectable differences in gene expression in endometria from pregnant and cyclic heifers on Days 5, 7, and 13 postestrus, but the expression of 764 genes was altered due to the presence of the conceptus at maternal recognition of pregnancy (Day 16). Of these 514 genes, MX2, BST2, RSAD2, ISG15, OAS1, USP18, IFI44, ISG20, SAMD9, EIF4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
247
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 260 publications
(266 citation statements)
references
References 86 publications
15
247
3
1
Order By: Relevance
“…In both cyclic and pregnant animals, similar changes occur in endometrial gene Maternal-embryonic interaction in early pregnancy expression up to initiation of conceptus elongation (approximately Day 13), suggesting that the default mechanism in the uterus is to prepare for, and expect, pregnancy (Forde et al, 2011b). Indeed, as mentioned above, it is possible to transfer an embryo to a synchronous uterus 7 days after oestrus and establish a pregnancy, as is routine in commercial bovine embryo transfer, and even up to Day 16.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…In both cyclic and pregnant animals, similar changes occur in endometrial gene Maternal-embryonic interaction in early pregnancy expression up to initiation of conceptus elongation (approximately Day 13), suggesting that the default mechanism in the uterus is to prepare for, and expect, pregnancy (Forde et al, 2011b). Indeed, as mentioned above, it is possible to transfer an embryo to a synchronous uterus 7 days after oestrus and establish a pregnancy, as is routine in commercial bovine embryo transfer, and even up to Day 16.…”
Section: Introductionmentioning
confidence: 95%
“…It is only when IFNT secretion from the conceptus is sufficient to induce the pregnancy recognition response in both the endometrium and in the extra uterine environment, that divergences between the pregnant and non-pregnant uterus are established. In general, these differences are detectable by Day 15 or Day 16 of pregnancy (Forde et al, 2011b;Bauersachs et al, 2012) and the major changes identified include response to a Type I Interferon, of which IFNT is one. This includes the up-regulation of 'classical' interferon-stimulated genes (ISGs) such as ISG15, (Johnson et al, 1998), MX1 and MX2 (Hicks et al, 2003), OAS1, BST2, B2M, CXCL10, STAT1, STAT2, PTX3, EIF4E, USP18 (Forde et al, 2011b) Indeed in the last number of years there have been quite a number of large transcriptomic studies performed on gene expression changes in the endometrium of pregnancy compared with non-pregnant or cyclic heifers.…”
Section: Conceptus-induced Effects On the Endometriummentioning
confidence: 99%
See 3 more Smart Citations